Anterior Cingulate Cortex to Ventral Hippocampus Circuit Mediates Contextual Fear Generalization - Bian, Xin-Lan; Qin, Cheng; Cai, Cheng-Yun; Zhou, Ying; Tao, Yan; Lin, Yu-Hui; Wu, Hai-Yin; Chang, Lei; Luo, Chun-Xia; Zhu, Dong-Ya (The Journal of neuroscience, 2019)
Contextual fear memory becomes less context-specific over time, a phenomenon referred to as contextual fear generalization. Overgeneralization of contextual fear memory is a core symptom of post-traumatic stress disorder (PTSD), but circuit mechanisms underlying the generalization remain unclear. We show here that neural projections from the anterior cingulate cortex (ACC) to ventral hippocampus (vHPC) mediate contextual fear generalization in male mice. Retrieval of contextual fear in a novel context at a remote time point activated cells in the ACC and vHPC, as indicated by significantly increased C-fos cells. Using chemogenetic or photogenetic manipulations, we observed that silencing the activity of ACC or vHPC neurons reduced contextual fear generalization at the remote time point, whereas stimulating the activity of ACC or vHPC neurons facilitated contextual fear generalization at a recent time point. We found that ACC neurons projected to the vHPC unidirectionally, and importantly, silencing the activity of projection fibers from the ACC to vHPC inhibited contextual fear generalization at the remote time point. Together, our findings reveal an ACC to vHPC circuit that controls expression of fear generalization and may offer new strategies to prevent or reverse contextual fear generalization in subjects with anxiety disorders, especially in PTSD. Overgeneralization of contextual fear memory is a cardinal feature of PTSD, but circuit mechanisms underlying it remain unclear. Our study indicates that neural projections from the anterior cingulate cortex to ventral hippocampus control the expression of contextual fear generalization. Thus, manipulating the circuit may prevent or reverse fear overgeneralization in subjects with PTSD.